An Australian Labour Market Conditions Index - Angelia Grant; Wilma Gillies; Ray Harris; Melissa Ljubic (The Australian Government, The Treasury, 2016)
This paper constructs a labour market conditions index for Australia using principal components analysis with 16 labour market variables. The index is broadly consistent with the business cycle in Australia. It shows that there was a large amount of slack in the Australian labour market during the global financial crisis and it has only recently returned to around average conditions. The index explains between 64 and 87 per cent of the variation in half of the labour market variables used in the analysis. The correlation between wage growth and the labour market conditions index is stronger than the correlation with the unemployment rate alone. In addition, the labour market conditions index appears to be a strong leading indicator of wage growth. The index is not sensitive to the addition of other variables.
Keywords: 330